DIPLOMASI INDONESIA UNTUK MENJADI TUAN RUMAH WORLD WATER FORUM KE-10 - Hikmah, Luthfiyyah Dorrotul; Renolafitri, Hendrini; Saeri, Mohammad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This research aims to examine how Indonesia used public diplomacy to be selected as host of the 10th World Water Forum, an effort to strengthen cooperation in the field of water and sustainable development, at the national, regional, and international levels. Through this framework, the study analyzes the public diplomacy steps taken by Indonesia to gain international support in the selection process for the 10th World Water Forum. This reasearch uses qualitative methods, with data collection techniques through literature studies sourced from books, journals, articles, news, and websites. This study uses the perspective of Liberalism and Nicholas J. Cull's public diplomacy theory, which consists of five main components: listening, advocacy, cultural diplomacy, exchange diplomacy, and international broadcasting. The results show that Indonesia was able to effectively implement all five components of public diplomacy. This strategy succeeded in building a positive image of Indonesia in the eyes of the world, thereby gaining significant support in the voting mechanism and ultimately being selected as host of the 10th World Water Forum. Keywords: Public diplomacy, Nation branding, World Water Forum